KONSEP GENDER DALAM AL-QURAN (Kajian Tafsir tentang Gender dalam QS. Ali Imran [3]:36) - Halim K, Abd. (AL-MAIYYAH, 2014)
This paper examines gender in the Quran, especially in QS. Ali Imran [3]: 36 with tahlili method. The interpretation of the concept of gender in these verses is the equality of women and men in doing any activity, especially in doing worship. The Quran gives spirit for all muslims to reproduce charity without distinction of sex. By doing worship to God, they further improve their safety, and for those who attain taqwa that is more precious in the sight of Allah.